Oxidative stress damage-associated molecular signaling pathways differentiate spontaneous preterm birth and preterm premature rupture of the membranes - Dutta, Eryn H; Behnia, Faranak; Boldogh, Istvan; Saade, George R; Taylor, Brandie D; Kacerovský, Marian; Menon, Ramkumar (Molecular human reproduction, 2016)
STUDY HYPOTHESIS: In women with preterm premature rupture of the membranes (PPROM), increased oxidative stress may accelerate premature cellular senescence, senescence-associated inflammation and proteolysis, which may predispose them to rupture. STUDY FINDING: We demonstrate mechanistic differences between preterm birth (PTB) and PPROM by revealing differences in fetal membrane redox status, oxidative stress-induced damage, distinct signaling pathways and senescence activation. WHAT IS KNOWN ALREADY: Oxidative stress-associated fetal membrane damage and cell cycle arrest determine adverse pregnancy outcomes, such as spontaneous PTB and PPROM. STUDY DESIGN, SAMPLES/MATERIALS, METHODS: Fetal membranes and amniotic fluid samples were collected from women with PTB and PPROM. Molecular, biochemical and histologic markers were used to document differences in oxidative stress and antioxidant enzyme status, DNA damage, secondary signaling activation by Ras-GTPase and mitogen-activated protein kinases, and activation of senescence between membranes from the two groups. MAIN RESULTS AND THE ROLE OF CHANCE: Oxidative stress was higher and antioxidant enzymes were lower in PPROM compared with PTB. PTB membranes had minimal DNA damage and showed activation of Ras-GTPase and ERK/JNK signaling pathway with minimal signs of senescence. PPROM had higher numbers of cells with DNA damage, prosenescence stress kinase (p38 MAPK) activation and signs of senescence. LIMITATIONS, REASONS FOR CAUTION: Samples were obtained retrospectively after delivery. The markers of senescence that we tested are specific but are not sufficient to confirm senescence as the pathology in PPROM. WIDER IMPLICATIONS OF THE FINDINGS: Oxidative stress-induced DNA damage and senescence are characteristics of fetal membranes from PPROM, compared with PTB with intact membranes. PTB and PPROM arise from distinct pathophysiologic pathways. Oxidative stress and oxidative stress-induced cellular damages are likely determinants of the mechanistic signaling pathways and phenotypic outcome. STUDY FUNDING AND COMPETING INTERESTS: This study is supported by developmental funds to Dr R. Menon from the Department of Obstetrics and Gynecology at The University of Texas Medical Branch at Galveston and funds to Dr M. Kacerovský from the Ministry of Health Czech Republic (UHHK, 001799906). The authors report no conflict of interest.
Keywords: signální transdukce; stanovení celkové genové exprese; Humans; Homeodomain Proteins; novorozenec nedonošený; superoxiddismutasa; Infant, Premature; Fetal Membranes, Premature Rupture; lidé; Mitogen-Activated Protein Kinase 1; Oxidative Stress; mitogenem aktivovaná proteinkinasa 3; těhotenství; Cellular Senescence; Infant, Newborn; Lamin Type B; lamin typ B; Signal Transduction; Gene Expression Profiling; Female; MAP kinasa-kinasa 4; extraembryonální obaly; Pregnancy; mitogenem aktivované proteinkinasy p38; p38 Mitogen-Activated Protein Kinases; DNA Damage; Premature Birth; předčasný porod; Superoxide Dismutase; stárnutí buněk; MAP Kinase Kinase 4; Adult; Mitogen-Activated Protein Kinase 3; dospělí; regulace genové exprese; Gene Expression Regulation; homeodoménové proteiny; novorozenec; mitogenem aktivovaná proteinkinasa 1; poškození DNA; předčasný odtok plodové vody; oxidační stres; ženské pohlaví; Extraembryonic Membranes